Innovations and Innovative Development as Factors of National Democratic Development (Zien Journal of Social Sciences and Humanities, 2023)
The article criticizes the old administration system and illustrates the innovative actions of Uzbek government to achieve a new national democratic development. The author gives the literature review to define the term of innovation and offers his own version. There is given the necessity of innovations in all spheres of life to construct a New Uzbekistan and shows the positive results of first innovative efforts to social and economic life of citizens. The foreign experience is given to show how economic changes help to develop national democracy. The author also defines the terms democracy and innovative pragmatism and emphasize the role of individuals to solve socio-economic problems.